Pest management through trap and border crops in vegetables - Kumari, Meenu; Pan, R S; Bhavana, P; Singh, A K (Indian Farming, 2023)
Ecological management of pests is a sustainable practical approach to achieve food security while protecting environment. The primary objective of Integrated Pest Management (IPM) is reducing input cost for pesticides and save ecosystem from harmful effect of pesticide residues. Many strategies like use of sticky and pheromone traps, early and delayed planting etc. are commonrecommendations while trap crop and border crop are unique with respect to managing enemies i.e. diverting crop enemies causing economic losses and enhancing natural enemies which are beneficial from ecosystem point of view with additional advantage of economic benefit from secondary crop. Therefore, trap and border crop are efficient, environment friendly and sustainable approach to manage insect-pests for commercial cultivation of vegetable crops.